2001
DOI: 10.1136/jmg.38.5.318
|View full text |Cite
|
Sign up to set email alerts
|

Atypical HNPCC owing to MSH6 germline mutations: analysis of a large Dutch pedigree

Abstract: Hereditary non-polyposis colorectal cancer (HNPCC) is the most common genetic susceptibility syndrome for colorectal cancer. HNPCC is most frequently caused by germline mutations in the DNA mismatch repair (MMR) genes MSH2 and MLH1. Recently, mutations in another MMR gene, MSH6 (also known as GTBP), have also been shown to result in HNPCC. Preliminary data indicate that the phenotype related to MSH6 mutations may diVer from the classical HNPCC caused by defects in MSH2 and MLH1.Here, we describe an extended Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
100
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(111 citation statements)
references
References 20 publications
8
100
1
2
Order By: Relevance
“…MLH1-and MSH2-deficient tumours are characterised by both mono-and dinucleotide repeat instability, whereas the level of MSI is lower in MSH6-deficient tumours (Bhattacharyya et al, 1995;Papadopoulos et al, 1995). MSH6-deficient cells are unable to repair single base mismatches, whereas they retain proficiency to repair two, three and four base loops (Drummond et al, 1995;Risinger et al, 1996;Umar et al, 1997), thus, causing only mononucleotide repeat instability in tumours (Wagner et al, 2001;Plaschke et al, 2004). Recently, EMAST and also low dinucleotide repeat instability have been associated with MSH3 deficiency both in tumour cell lines and in sporadic colorectal tumours (Haugen et al, 2008).…”
mentioning
confidence: 99%
“…MLH1-and MSH2-deficient tumours are characterised by both mono-and dinucleotide repeat instability, whereas the level of MSI is lower in MSH6-deficient tumours (Bhattacharyya et al, 1995;Papadopoulos et al, 1995). MSH6-deficient cells are unable to repair single base mismatches, whereas they retain proficiency to repair two, three and four base loops (Drummond et al, 1995;Risinger et al, 1996;Umar et al, 1997), thus, causing only mononucleotide repeat instability in tumours (Wagner et al, 2001;Plaschke et al, 2004). Recently, EMAST and also low dinucleotide repeat instability have been associated with MSH3 deficiency both in tumour cell lines and in sporadic colorectal tumours (Haugen et al, 2008).…”
mentioning
confidence: 99%
“…It is intriguing that the only gene showing no mutation in this cases was MSH6, a gene usually described as associated with LS with EC phenotype. 41,44 It is also of notice that four female patients with CRC underwent prophylactic hysterectomy and adnexectomy, a valid option for LS female patients in menopause or perimenopausal, after informed consent.…”
Section: 23mentioning
confidence: 99%
“…41,44 That is considered to be the principal clinical manifestation for female patients with this mutation. 42,44 They are usually diagnosed in patients over 50 years of age 41,44 and it was observed that at the age of 70, 71% of female patients with this mutation will have EC. 44 Along with MSH2, MSH6 mutation is more related to EC than mutations in MLH1 or PMS2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to most mutations affecting the MLH1 and MSH2 genes, a significant proportion of MSH6 mutations occur in HNPCC families with less typical clinical features. Carriers of MSH6 mutations often display late age at onset, carcinomas of the endometrium, and low or no microsatellite instability (MSI) in tumours (Miyaki et al, 1997;Kolodner et al, 1999;Wijnen et al, 1999;Wu et al, 1999;Parc et al, 2000;Wagner et al, 2001;Berends et al, 2002;Peterlongo et al, 2003;Cederquist et al, 2004). Moreover, one-third of MSH6 mutations are nontruncating, and so do not necessarily destroy the encoded protein.…”
mentioning
confidence: 99%